2018
DOI: 10.4102/ajlm.v7i2.770
|View full text |Cite|
|
Sign up to set email alerts
|

Antimicrobial resistance surveillance in Ethiopia: Implementation experiences and lessons learned

Abstract: IntroductionAntimicrobial resistance (AMR) poses a global threat. High levels of AMR to commonly used antibiotics have been reported in East Africa. A situation analysis of AMR in Ethiopia also indicated high resistance levels. To prevent and contain AMR, Ethiopia established a national surveillance network.ObjectivesThis article describes the steps taken to prioritise AMR and establish the National Antimicrobial Resistance Surveillance System in Ethiopia, as well as present the challenges and lessons learned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 4 publications
3
40
0
1
Order By: Relevance
“…These findings suggested that the issue of antimicrobial resistance has not yet been resolved in Ethiopia. Antibiotic resistance has become a major public health threat throughout the globe, which requires collaborative intervention [ 33 ]. The main factors that contribute to antimicrobial resistances include mutations in bacterial genomes, inappropriate use of antibiotics, poor drug regulation policies, improper drug prescription, and disobedience to prescription [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that the issue of antimicrobial resistance has not yet been resolved in Ethiopia. Antibiotic resistance has become a major public health threat throughout the globe, which requires collaborative intervention [ 33 ]. The main factors that contribute to antimicrobial resistances include mutations in bacterial genomes, inappropriate use of antibiotics, poor drug regulation policies, improper drug prescription, and disobedience to prescription [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Six of the reviewed SRs and MAs (three moderate [20,25,26] and three critically low quality [21,22,24]) revealed significantly high resistance of erythromycin (30-97.6%). According to the FMHACA national baseline, AMR surveillance reported that the resistance of Streptococcus pneumonia, the most common cause of CAP, to erythromycin increased from 0% in 1996 to 19.2% in 2000 [9]. In Ethiopia, where clinicians are not supported by basic bacteriology services to ensure that treatment is tailored to the specific condition, information deduced from such pooled data is crucial in principle.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infections are the major cause of death in Ethiopia, and antibacterial resistance threatens the management of bacterial infection in the health care setting [8]. The first national AMR baseline survey (2009) revealed that most bacteria causing common infections in humans showed considerable resistance to commonly used first-line antibacterial agents [9]. The country's Medicine and Health Care Administration and Control Authority (FMHACA), currently called the EFDA (Ethiopia Food and Drug Administration), has established STGs for the three levels of the health care system (health centers, primary and general hospitals) since 2004 and has an updated third edition [10].…”
Section: Introductionmentioning
confidence: 99%
“…Institutions that have successfully implemented programs to curb inappropriate antimicrobial prescribing have done so through interdisciplinary clinician education, protocol development, and ongoing reviews of guideline adherence [4,5]. Establishment of these antimicrobial stewardship (AMS) interventions has been developed in multiple LMICs [6][7][8][9][10]. Specifically in African nations, AMS implementation has been limited but successful in several published reports, although these programs have additional challenges [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%